2020
DOI: 10.3390/pharmaceutics12050424
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Intracellular Hyperthermia of Iron Oxide Magnetic Nanoparticles, Synthesized at High Temperature by a Polyol Process

Abstract: We report the synthesis of magnetite nanoparticles (IOMNPs) using the polyol method performed at elevated temperature (300 °C) and high pressure. The ferromagnetic polyhedral IOMNPs exhibited high saturation magnetizations at room temperature (83 emu/g) and a maximum specific absorption rate (SAR) of 2400 W/gFe in water. The uniform dispersion of IOMNPs in solid matrix led to a monotonous increase of SAR maximum (3600 W/gFe) as the concentration decreased. Cytotoxicity studies on two cell lines (cancer and nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 90 publications
12
46
1
Order By: Relevance
“…These values were chosen based on EMR and hyperthermia studies reported in the literature. 2,41,42 It was observed no difference in the EMR spectra for all the concentrations evaluated ( Fig. 7C), which evidenced the absence of interparticle interactions even with a 50-fold variation in concentration.…”
Section: Nanoscale Advances Accepted Manuscriptmentioning
confidence: 81%
“…These values were chosen based on EMR and hyperthermia studies reported in the literature. 2,41,42 It was observed no difference in the EMR spectra for all the concentrations evaluated ( Fig. 7C), which evidenced the absence of interparticle interactions even with a 50-fold variation in concentration.…”
Section: Nanoscale Advances Accepted Manuscriptmentioning
confidence: 81%
“…As in MHT there are two heat sources depending on nanoparticle location (surrounding tissue or cells and intracellular) [ 39 , 40 , 41 ], it is important to associate both sources to optimize MHT therapy. In this sense, the present study aims to improve the nanoparticles internalization process in C6 cells using different strategies such as static and dynamic magnetic fields, as well as transfection agent such as PLL, assisted by filtering process of SPION Amine , and it was possible to observe that SPION Amine (100 nm) were internalized in C6 cells more efficiently using magnetic field (magnetofection), associated with the transfection agent PLL.…”
Section: Discussionmentioning
confidence: 99%
“…The basic principle of the polyol method was explained by Caruntu et al [ 36 ], as a two-step procedure; first, the formation of the hydroxides, followed by metal centres chelation. Through simple optimization of the operating synthesis conditions—namely, the nature of the magnetic precursors and precipitator, the solvents’ nature, the addition of an extra stabilizer, and the temperature, pressure and duration of the reaction—the metal nanoparticles features can be tailored for the targeted application [ 37 , 38 ]. Compared with thermal decomposition or co-precipitation methods, the polyol process yields nanoparticles with a narrow particle size distribution in a simple, environmentally friendly, reproducible and cost-effective way, without the need for an inert atmosphere [ 39 ].…”
Section: Techniques For Synthesis Of Iron Oxide Core For Imaging Purposesmentioning
confidence: 99%